Vasotoxic Effects of Anticancer Therapy: a Review of Current Data - Yu. A. Vasyuk; E. Y. Shupenina; A. G. Nosova; E. O. Novosel; D. A. Vyzhigin (Столичная издательская компания, 2023)
Cardiovascular and oncological diseases are the leading causes of adult death in the world. Despite proven efficacy, anticancer drugs can cause severe cardiovascular complications. Recently, data have appeared on the possible vasotoxic effects of chemotherapy drugs, which can manifest themselves as the progression of arterial hypertension and atherosclerosis, the development of myocardial ischemia and acute coronary syndrome, the formation of venous and arterial thrombosis. The key mechanism for the development of vasotoxicity is endothelial dysfunction, and anticancer drugs can also affect the processes of thrombosis. The review presents the results of 12 selected observational retro- and prospective studies involving cancer patients receiving presumably vasotoxic therapy. Data on the frequency of occurrence and possibilities for the prevention of vasotoxicity are presented.